h.hofstede (h.hofstede@hogeland.nl)

       
1. a. √1620 = √(2 2 3 3 3 3 5) = 2335  = 18√5  
  b. √176 = √(2 2 2 2 11) = 22√11 = 4√11  
  c. √1575 = √(3 3 5 5 7) = 35√7 = 15√7  
  d. √5265 = √(3 3 3 3 5 13) = 33√(513) = 9√65  
  e. √5832 = √(2 2 2 3 3 3 3 3 3) = 2333√2 = 54√2  
  f. √5445 = √(3 3 5 11 11) = 311√5 = 33√5  
  g. √4732 = √(2 2 7 13 13) = 213√7 = 26√7  
  h. √1792 = √(2 2 2 2 2 2 2 2 7) = 2222√7 = 16√7  
  i. √1296 = √(2 2 2 2 3 3 3 3 ) = 2 2 3 3 = 36  
  j. √7203 = √(3 7 7 7 7) = 77√3 = 49√3  
       
2. a.  
       
  b.  
       
  c.  
       
  d.
       
  e.  
       
  f.
       
  g.
       
  h.
       
3. a. √180 + √20 = √(36 5) + (4 5) = 36 5 + 4 5 = 65 + 25 = 85
       
  b.  
       
  c. √192 + √75 - √27 = √(64 3) + (25 3) - (9 3)
=
64 3 + 25 3 - 9 3 = 83 + 53 - 33 = 103
 
       
  d.  
       
  e.
       
  f.  
       
4.
  f(1) = 1/2(√2 - √0)
f(3) = 1/2(√4 - √2)
f(5) = 1/2(√6 - √4)
enz.
Dat geeft:
f(1) + f(3) + f(5) + ... + f(99)
=
1/2( (√2 - √0) + (√4 - √2) + (√6 - √4) + ... + (√100 - √98) )
alles valt weg behalve de √0 en de √100.
dus komt er uit:  1/2(-√0 + √100) = 5 
       
5.  (5 + 6 + 7)(5 + 6 - 7)(5 - 6 + 7)(-5 + 6 + 7)
(55 + 56 - 57 + 65 + 66 - 67 + 75 + 76 - 77)(5 - 6 + 7)(-5 + 6 + 7)
=  (5 + 230  + 6 - 7)(5 - 6 + 7)(-5 + 6 + 7)
=  (4 + 230)(5 - 6 + 7)(-5 + 6 + 7)
(4 + 230)(-55 + 56 + 57 - 65 - 66 - 67 - 75 + 67 + 77)
=  (4 + 230)(-5 - 6 + 7 + 230)
=
 (4 + 230)(-4 + 230)
=  -16 + 120
=  104
       

h.hofstede (h.hofstede@hogeland.nl)